An Analysis of Teachers’ Challenges in Teaching Speaking Through Online Learning during Covid-19 Pandemic in SMAN 2 Abiansemal - Putra Maha Anugrah (English Education Department STKIP Agama Hindu Singaraja, 2021)
ABSTRACT This research aims at at finding out 1) the challenges of the teachers in teaching speaking during online learning in SMAN 2 Abiansemal, 2) the teachers’ ways to cope with the challenges in teaching speaking during online learning in SMAN 2 Abiansemal and 3) the strengths and the weaknesses of the strategy used by the investigated teachers during online learning in teaching speaking. The subjecs of this research were three English teachers in SMAN 2 Abiansemal. To collect the data, two instruments were needed, observation sheet and interview guide. The obtained data were analyzed qualitative by using Interactively Data Analysis Model by Miles and Huberman (1994). This research discovers 1) 9 challenges in online learning, 2) 9 ways to cope the challenges, and 3) 9 weaknesses and strengths of the strategy.